1999
DOI: 10.1088/0305-4470/32/14/009
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries of the discrete Burgers equation

Abstract: A discrete Cole-Hopf transformation is used to derive a discrete Burgers equation that is linearizable to a discrete heat equation. A five-dimensional symmetry algebra is obtained that reduces to the Lie point symmetry algebra of the usual Burgers equation, in the continuous limit. This Lie algebra is used to obtain explicit invariant solutions. RésuméOn utilise une transformation de Cole-Hopf pour obtenir uneéquation de Burgers discrète qui est linéarisable et peutêtre ainsi amenéeà uneéquation de la chaleur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…To this end, it is convenient to write down the scheme in terms of unm . We then have the discrete Burgers equation trueunm+1unm=1+δε2un+1m2+1unm+κm0.16em()un+1m1unm1+δε2unm2+1un1m+κm0.16em()unm1un1m,κm=ε(Rmβ)2a12,n=1,,N1,1emm=0,1,2,,with initial condition un0=12a12bεμn(0)1+2a12bεμn(0),n=0,2,N1,and the boundary conditions u0m=1κm2aε2false(1+κ...…”
Section: Integrable Discrete Modelsmentioning
confidence: 99%
“…To this end, it is convenient to write down the scheme in terms of unm . We then have the discrete Burgers equation trueunm+1unm=1+δε2un+1m2+1unm+κm0.16em()un+1m1unm1+δε2unm2+1un1m+κm0.16em()unm1un1m,κm=ε(Rmβ)2a12,n=1,,N1,1emm=0,1,2,,with initial condition un0=12a12bεμn(0)1+2a12bεμn(0),n=0,2,N1,and the boundary conditions u0m=1κm2aε2false(1+κ...…”
Section: Integrable Discrete Modelsmentioning
confidence: 99%
“…Similar techniques can be applied to the previously introduced Burgers' equation (1). In Heredero, Levi, and Winternitz (1999) it is shown that the standard Burgers' equation with = 1,…”
Section: Parameter Function = (X)mentioning
confidence: 99%
“…Heredero et al (1999) showed that the standard Burgers' equation with parameters set to 1, u t = u xx + 2uu x (4) can be transformed into the Potential Burgers' equation by using the transformation u = v x , resulting in v tx = v xxx + 2v x v xx . After integrating this expression we obtain…”
Section: Preliminariesmentioning
confidence: 99%